Genetika Populasi dan Strategi Konservasi Badak Jawa (Rhinoceros sondaicus Desmarest 1822) (Population Genetics of Javan Rhino (Rhinoceros sondaicus Desmarest 1822) and It’s Conservation Strategy) - U Mamat Rahmat (Jurnal Manajemen Hutan Tropika, 2009)
Javan rhino (Rhinoceros sondaicus Desmarest 1822) of which spread is limited in Indonesia and Vietnam is the rarest species among 5 species of rhino in the world. Without appropriate and long-term well organized management action, the population of javan rhino will be in extinction. This research studies about the usage potential of  javan rhino population genetics data in designing  javan rhino conservation program. The application of genetics study in conservation problem is based on the population genetics theory. The population genetics is one of population biology branch which studies about the factors determining genetic composition of population and how they play role in evolution process. The genetic characteristic identification can help to give the characteristic genetic information which has function as genetic marker or gen in javan rhino management. It can also help to do translocation the javan rhino especially for breeding management effort to avoid inbreeding and to improve the heterozygosis. The analyzing result shows that the management of conservation strategy which can make javan rhino population reaches the population viable minimum number is needed urgently. Furthermore, it also shows that translocation and reintroduction to build the second population of  javan rhino is also important to do.    Keywords: javan rhino, population genetics, translocation, second population